Hubungan Kondisi Lingkungan, Kebiasaan Merokok Orang Tua dan Perilaku Cuci Tangan dengan Kejadian Infeksi Saluran Pernapasan Akut pada Anak di RSUD Matraman: Correlation between Environmental Conditions, Parents' Smoking Habits and Handwashing Behavior with the Incidence of Acute Respiratory Infections in Children at Matraman Hospital - Gandaria, Pebrina (MPI Press, 2023)
Introduction: Acute respiratory infections in toddlers are caused by factors such as the condition of the home environment and toddler factors (nutritional status, exclusive breastfeeding, completeness of immunization, baby's age and low birth weight). Conditions in the home environment that can affect the air quality in the house can trigger the occurrence of Acute Respiratory Infections (ARI), including environmental tobacco smoke or affect cigarette smoke in the house. Objective: To determine the relationship between environmental conditions, parents' smoking habits and hand-washing behavior with the incidence of ARI in children at Matraman Hospital Methods: The research design is analytic with a cross-sectional approach. In this study, the population was 58 children who experienced acute respiratory infections at the Matraman Hospital. The sampling technique used Accidental sampling. the research instrument used a questionnaire/questionnaire and was analyzed using the Chi-Square Test. Results: Based on the results of the Chi-Square test, it was found that there was a relationship between environmental conditions and the incidence of ARI in children with a P-value = 0.017 and an OR value of 4.615. The relationship between parents' smoking habits at home and the incidence of ARI in children has a P-value = 0.001 and an OR value of 8.640. The relationship between handwashing behavior at home and the incidence of ARI in children has a P-value = 0.003 and OR 6.750. Conclusion: The description of the results of the study was that in most of the incidents of mild ARI, environmental conditions were good, parents' smoking habits at home were good and hand-washing behavior at home was good. There is a relationship between environmental conditions, parents' smoking habits at home and hand-washing behavior at home with the incidence of ARI in children at Matraman Hospital. The most influential factor in the incidence of ARI in children at Matraman Hospital is parents' smoking habits at home